VISUAL ARTS, TECHNOLOGY, AND SOCIAL CHANGE: A MULTIDISCIPLINARY PERSPECTIVE - Sripada, Pushpa Nagini; K, Priyadharshini; R, Jeevajothi; D, Ganesh Kumar; S, Prathiba; Arumugam, Mahendran (ShodhKosh: Journal of Visual and Performing Arts, 2026)
With the rapid evolution of the digital technologies, the situation related to the visual arts has significantly altered, allowing the creative process of expression to be offered in a new form and enlarging the opportunities of the art as a social activity. This multidisciplinary relationship of visual arts, technology and social change will be discussed in this paper. The paper addresses the changes of creative activities and the ability to tell social stories in artistic works with the appearance of new technologies such as artificial intelligence, virtual reality, augmented reality, interactive media, and digital platforms. The modern visual art projects will be able to involve the community through the artistic creativity and technology innovation that will result in the creation of awareness of social issues and cultural discourse. The paper begins with a literature background and evolution of visual arts in the digital era. A thorough analysis of the recent literature is conducted to discuss the existing practices of art which technologies implement: digital art, AI-generated art, immersive multimedia installation, and participatory art projects. Based on the analysis, the pros and cons of the current approaches are identified and taken into account in comparison with the elements of accessibility, the ability to engage the audience and make a social impact. A comparative analysis is also provided in an attempt to evaluate different technology-based art models, which have been evaluated based on the impact of communication, community interaction, and malleability of the technology. These findings form the basis of the paper and propose a multidisciplinary framework of integration of visual arts, digital technologies, and social interaction. The framework draws a system architecture involving an innovative content creation, technology assimilation, interactive engagement and social impact analysis. The proposed model will help the artist, researchers and policy makers to develop technology based visual art projects that can positively transform society. The results also show how the potential of technology-based visual arts can be used to empower locals, raise awareness of culture, and support policy and educational endeavors. The study comes to the conclusion that the strategic union of art and technology can be topical in the context of overcoming the contemporary social issues and facilitating the inclusive cultural development.